STATE FORMATION AND DISPUTE RESOLUTION MECHANISM IN ETHIOPIA: A CASE OF WOLAITTA PEOPLE - Tariku, Ayele (European Scientific Journal, ESJ, 2015)
The need for the study of the state formation, succession, kinship, customary dispute resolution mechanisms, social stratification, and other related concepts in Ethiopia and the Horn of Africa are becoming the inquiry of today. This paper is basically set out to address state formation and the customary conflict resolution practice of the Wolaita societies who are one of the many ethnic groups in Ethiopia. Methodologically, this paper has made use of both secondary and primary data sources with much emphasis on the latter. Accordingly, I conducted a series of an in-depth interview with twelve Wolaita informants (out of whom two were females), who are selected on the basis of their knowledge they possess about the issue at hand and also based on their willingness. Oral sources and literature crosschecked and triangulated. As an investigation of the major sources for the study of state formation and customary conflict resolutions, this paper will help intellectuals for further studies on issues in Ethiopia in particular and Africa in general. The findings put forward that Wolaita reached the stage of state formation through the processes of immigrations and integration about 13 and 14th century AD. Agriculture, trade, population pressure, the threat of war and the influence of previously existing states were as very common causes for early state formation of the Wolaita. The institutions of justice of the kingdom were proved weak in higher level, which was collapsed with the conquest of Menelik II in the late 19th century, while local based dispute settlement which is still alive and orient to clan advantages is proved stronger bringing a last solutions to dispute though ritual elements of dispute settlement process.